2002
DOI: 10.1111/j.1939-1676.2002.tb02343.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stress Hyperglycemia in Cats Is Associated with Struggling and Increased Concentrations of Lactate and Norepinephrine

Abstract: We characterized the changes in blood glucose concentrations in healthy cats exposed to a short stressor and determined the associations between glucose concentrations, behavioral indicators of stress, and blood variables implicated in stress hyperglycemia (plasma glucose, lactate, insulin, glucagon, cortisol, epinephrine, and norepinephrine concentrations). Twenty healthy adult cats with normal glucose tolerance had a 5-minute spray bath. Struggling and vocalization were the most frequent behavioral responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
159
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(173 citation statements)
references
References 21 publications
8
159
1
5
Order By: Relevance
“…Since only healthy animals were used for this study, counteracting hormones, such as glucagon but also norepinephrine (Rand et al, 2002), might have played a substantial role in preventing hypoglycaemia or even slight drops in blood glucose concentrations. A recent study in healthy rats showed an unexpected rise of glucose levels after acute administration of exenatide caused by stimulation of the sympathetic nervous system (Perez-Tilve et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Since only healthy animals were used for this study, counteracting hormones, such as glucagon but also norepinephrine (Rand et al, 2002), might have played a substantial role in preventing hypoglycaemia or even slight drops in blood glucose concentrations. A recent study in healthy rats showed an unexpected rise of glucose levels after acute administration of exenatide caused by stimulation of the sympathetic nervous system (Perez-Tilve et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There are likely a number of significant relationships that remain to be found between struggling and other physiological and neural changes induced by restraint. There is already a literature indicating that greater amounts of struggling during immobilization is associated with altered immune system functioning [2], increased severity of gastric ulcers [14,27], increased lactate levels in blood [22] and lactic acid in muscle indicative of hyperglycemia and metabolic acidosis [7]. In these studies the amount of struggling observed was directly related to the severity of negative stress-induced physiological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, under stressful states, epinephrine depresses insulin secretion and activates beta receptors of pancreatic alpha cells, and stimulates glucagon production (Hadley and Levine 2007). Restraint for 1h (Zardooz et al 2006), water immersion (Radahmadi et al 2006) in the rats, and water spray bath for 15 minutes in the cats (Rand et al 2002) resulted in increased serum glucose levels. In the present study, elevated serum glucose was decreased with dietary melatonin supplementation.…”
Section: Discussionmentioning
confidence: 97%